(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To develop an overview of the diagnosis, approach, and treatment of Female genital – pelvic pain dysfunction. Subject and method: Synthesis and analysis of studies on Female genital – pelvic pain dysfunction and the latest guidelines on diagnosis and treatment of the International Society for the Study of Women’s Sexual Health, The International Society for the Vulvovaginal Disease, The International Pelvic Pain Society. Results: Complete an update on the diagnosis and treatment of Female genital – pelvic pain dysfunction. Conclusions: The ISSVD, ISSWSH, and IPPS adopted a new vulvar pain and vulvodynia terminology, divides vulvar pain into two overarching categories: Vulvar pain related to a specific disorder and Vulvodynia. Pelvic genitourinary examination should be performed in all patients. Treatments should be individualized, and a multimodal treatment approach to address all aspects of pain is recommended. If appropriate, should start with conservative medical non-invasive approaches. It will rarely be necessary to escalate to surgical interventions.